FAKTOR-FAKTOR KESULITAN BELAJAR SISWA KELAS IV PADA MATA PELAJARAN IPS DI SD NEGERI 1 PENANGGOAN DUREN KABUPATEN OKI - Hengki Juliartha; Muhamad Idris; Ida Suryani (JS (JURNAL SEKOLAH), 2022)
Abstract : The goal to be achieved in this study is to find out the factors of learning difficulties of grade IV students in social studies subjects in SDN 1 OIC District Duren. the results of research that has been carried out by researchers, then analyze the results of questionnaires and interviews of students, in social studies subjects of Heroism and Patriotism material in grade IV SDN 1 Penanggoan Duren. Results Based on 27 students there are around 81-100% with the number of 5 student categorized as very strong ability to have inhibiting factors in social studies learning, this is because students have indicators from internal and external aspects that are very strong in influencing to be an inhibiting factor in social studies learning. Furthermore, there are 61-80% with a total of 13 students categorized as Strong abilities have obstacles in social studies learning, so that internal and external indicators greatly affect the constraints of social studies learning. Then there is the 41-60% category with a total of 9 students with sufficient categories because students have a slight obstacle in social studies learning which looks quite an obstacle to the factors of social studies learning difficulties.Keywords; Analysis, Inhibiting Factors, Learning DifficultiesAbstrak : Tujuan yang ingin dicapai dalam penelitian ini adalah untuk mengetahui faktor-faktor kesulitan belajar siswa kelas IV pada Mata pelajaran IPS di SDN 1 Penanggoan Duren  Kabupaten OKI. Hasil penelitian yang telah dilakukan peneliti maka analisis hasil angket dan wawancara peserta didik, pada mata pelajaran IPS materi Kepahlwanan dan Patriotisme pada kelas IV SDN 1 Penanggoan Duren. Hasil Berdasarkan dari 27 siswa terdapat sekitar 81-100% dengan jumlah 5 orang siswa dikategorikan berkemampuan sangat kuat memiliki faktor pengahambat dalam pembelajaran IPS, hal ini dikarenakan siswa memiliki indikator dari segi internal dan eksternalnya sangat kuat mempengaruhi menjadi faktor penghambat dalam pembelajaran IPS. Selanjutnya terdapat 61-80% dengan jumlah 13 orang siswa dikategorikan berkemampuan Kuat memiliki penghambat dalam pembelajaran IPS, sehingga indikator Internal dan ekseternalnya sangat mempengaruhi dalam kendala pembelajaran IPS. Kemudian terdapat kategori 41-60% dengan jumlah 9 orang siswa dengan kategori cukup dikarenakan siswa memiliki sedikit penghambat dalam pembelajaran IPS dimana terlihat cukup sebagai penghambat faktor-faktor kesulitan belajar IPS.Kata Kunci; Analisis, Faktor Penghambat, Kesulitan Belajar